Primary flap closure in alveolar ridge preservation for periodontally damaged extraction socket: A randomized clinical trial. (14th December 2022) - Seo, Gil‐Jong; Lim, Hyun‐Chang; Chang, Dong‐Wook; Hong, Ji‐Youn; Shin, Seung‐Il; Kim, Gyutae; Shin, Seung‐Yun
Abstract: Introduction: The effect of primary wound closure (PC) on alveolar ridge preservation (ARP) in periodontally damaged sockets has yet to be fully discovered. Methods: Periodontally damaged sockets were allocated to one of the following groups: (1) ARP with PC (group PC), and (2) ARP without PC (group secondary wound closure [SC]). Following tooth extraction and flap elevation, granule‐type xenogeneic bone substitute material and a collagen barrier were applied. Ridge change was evaluated using cone‐beam computed tomographic (CBCT) scans immediately after ARP and at 4 months. Core biopsy specimens were examined histomorphometrically. Results: A total of 28 patients were included in the analysis (13 in group PC, 15 in group SC). Histomorphometrically, the percentage of newly formed bone was 26.2 ± 17.7% and 24.6 ± 18.4% in groups PC and SC, respectively (independent t ‐test, degree of freedom [df]  =  25, p  > 0.05). Horizontal ridge changes on CBCT were −4.9 ± 3.1 mm and − 4.2 ± 2.5 mm in groups PC and SC at the 1 mm level below the ridge crest, respectively (independent t ‐test, df  =  26, p  > 0.05). Approximately half of the sites required additional bone augmentation at implant placement. Conclusions: ARP with/without PC yielded similar new bone formation and radiographic ridge change. This clinical trial was not registered prior to participant recruitment and randomization (https://cris.nih.go.kr/cris/search/detailSearch.do/19718 ).